Pengaruh Persepsi Resiko, Kualitas Layanan, Kemudahan Penggunaan, Dan Kepercayaan Terhadap Keputusan Pembelian Pada E-Commerce Tokopedia (Studi Kasus Pada Mahasiswa Fakultas Ekonomi Dan Bisnis Universitas Islam Malang Angkatan 2020) - Zayyana Wardah, Zalfaa Bilqis Nurfaihaa; Khalikussabir, Khalikussabir; Rahman, Fahrurrozi (UNIVERSITAS ISLAM MALANG, 2024)
Abstract This research was conducted to determine the influence of perceived risk, service quality, ease of use and trust on Tokopedia e-commerce purchasing decisions. This research method uses a quantitative method using a proportional random sampling technique, namely a random sampling technique and the data source used is primary data with data collection using a Likert scale questionnaire for consumers who have made purchases on Tokopedia e-commerce. The sample calculation in this study used the Slovin formula which produced 87 respondents. The data analysis used is descriptive analysis, instrument testing, classical assumptions, multiple linear regression analysis and hypothesis testing using SPSS 25 for Windows. The results of this research show that risk perception, service quality, trust in use and trust simultaneously and partially influence purchasing decisions in Tokopedia e-commerce. Keywords : Risk Perception, Service Quality, Ease of Use, Trust and Purchasing Decision